2014
DOI: 10.1128/jvi.01833-14
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection with Streptococcus pneumoniae Modulates the B Cell Response to Influenza Virus

Abstract: Pathogen-specific antibodies (Abs) protect against respiratory infection with influenza A virus (IAV) and Streptococcus pneumoniae and are the basis of effective vaccines. Sequential or overlapping coinfections with both pathogens are common, yet the impact of coinfection on the generation and maintenance of Ab responses is largely unknown. We report here that the B cell response to IAV is altered in mice coinfected with IAV and S. pneumoniae and that this response differs, depending on the order of pathogen e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 70 publications
3
30
1
Order By: Relevance
“…Recently, Wolf et al also reported that coinfection could modulate the B cell response and demonstrated that sequential infection with influenza virus followed by pneumococcus increased the antibody response to influenza virus (20). The discrepancy in results between the study by Wolf et al and the current study could be due to the different infectious models being used.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Recently, Wolf et al also reported that coinfection could modulate the B cell response and demonstrated that sequential infection with influenza virus followed by pneumococcus increased the antibody response to influenza virus (20). The discrepancy in results between the study by Wolf et al and the current study could be due to the different infectious models being used.…”
Section: Discussioncontrasting
confidence: 56%
“…Notably, the study of Wolf et al (20), on day 10 post-PR8 infection, coinfected mice had lower virus-specific IgG amounts in the lung, as well as fewer Tfh and GCB cells in mLN although there was no statistical significance. On the other hand, the current study used a lethal coinfection model and provided an earlier kinetics, showing that on day 8 post-PR8 infection, the virus-specific IgG, IgM, and IgA levels in the lung, as well as the related cellular support from the lung, mLN, and spleen, including Tfh, GCB, and plasma cells, were significantly decreased.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Whereas Wolf et al (2014) described increased levels of virus-specific IgG in a rather mild murine model of postinfluenza bacterial pneumonia, others found a severe impairment of IgG, IgM and IgA production in co-infected mice (Wu et al, 2015). These contrasting findings have mainly been explained with differences in the experimental models (sub-lethal vs lethal co-infection).…”
Section: Impairment Of Antibody-mediated Immunitymentioning
confidence: 74%